1989
DOI: 10.1159/000281444
|View full text |Cite
|
Sign up to set email alerts
|

Does Medical Therapy Cure Female Stress Incontinence?

Abstract: Forty-four consecutive female patients, who were scheduled for operation for genuine stress incontinence but instead treated pharmacologically with an Α-agonist or placebo for 3–4.5 months, were evaluated after a median observation period of 30 months. Ten patients (23%) underwent colposuspension. Fourteen patients (32%) claimed to be continent or so much improved that further treatment was considered unnecessary by the patients themselves. Of the remaining 20 patients who still claimed to have stress incontin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…It is reported that α‐adrenergic receptors exist in neurons and ganglions in the bladder trigone and posterior urethra, and stimulation inhibits bladder contracrtion 10,19 Thus, imipramine having both α‐agonist and anti‐cholinergic effects might act both by increasing urethral pressure and decreasing bladder contractility by enhancing the bladder compliance, as shown in this present study. The duration of treatment was three months because many other studies have adopted this amount of time 2,3 . Our results showed that 35% (95% CI 15–55) of women with genuine stress incontinence were cured and 25% (95% CI 8–42) improved by 2 50% by pad weight after imipramine treatment.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…It is reported that α‐adrenergic receptors exist in neurons and ganglions in the bladder trigone and posterior urethra, and stimulation inhibits bladder contracrtion 10,19 Thus, imipramine having both α‐agonist and anti‐cholinergic effects might act both by increasing urethral pressure and decreasing bladder contractility by enhancing the bladder compliance, as shown in this present study. The duration of treatment was three months because many other studies have adopted this amount of time 2,3 . Our results showed that 35% (95% CI 15–55) of women with genuine stress incontinence were cured and 25% (95% CI 8–42) improved by 2 50% by pad weight after imipramine treatment.…”
Section: Discussionmentioning
confidence: 67%
“…Women with genuine stress incontinence require individual evaluation in the choice of treatment, depending on the degree of genuine stress incontinence and past experience of treatment. Although surgical intervention is the most common treatment for women with genuine stress incontinence, the fact that more than 100 difffer‐ent surgical procedures have been described 1 shows that surgical treatment is not always satisfactory 2,3 . These procedures can lead to dysfunction of the lower urinary tract in the form of impaired voiding, residual urine, recurrent urinary infection, detrusor instability, dyspare‐unia, low abdominal pain or enterocele 3–5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Norfenefrine possesses a favorable profile of effect and side effects in the treatment of SI. A recent study has demonstrated the effect of norfenefrine even in patients with severe SI [4], and previously published data indicate that the routine use of norfenefrine prior to planned surgery may reduce the number of operations [23].…”
Section: Discussionmentioning
confidence: 97%
“…Insbesondere angesichts der jüngsten Diskussionen um das allgemeine Nutzen-Risiko-Profil systemischer Östrogenbehandlung bei menopausalen Frauen können sie deshalb zur Behandlung der Stressinkontinenz nicht empfohlen werden. (5,12,27,30,31,37).…”
Section: öStrogeneunclassified